2019
DOI: 10.3390/cells8070689
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid Evokes an Increase in Intracellular Ca2+ Concentration and Nitric Oxide Production in Endothelial Cells from Human Brain Microcirculation

Abstract: It has long been known that the conditionally essential polyunsaturated arachidonic acid (AA) regulates cerebral blood flow (CBF) through its metabolites prostaglandin E2 and epoxyeicosatrienoic acid, which act on vascular smooth muscle cells and pericytes to vasorelax cerebral microvessels. However, AA may also elicit endothelial nitric oxide (NO) release through an increase in intracellular Ca2+ concentration ([Ca2+]i). Herein, we adopted Ca2+ and NO imaging, combined with immunoblotting, to assess whether A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 73 publications
5
38
0
Order By: Relevance
“…The antioxidative effects of HZTF may partially account for the underlying mechanism. NO and ROS, which are affected by the activation of the arachidonic acid pathway [ 58 , 59 ], were also significantly inhibited by HZTF as demonstrated in our in vitro experiments.…”
Section: Discussionsupporting
confidence: 70%
“…The antioxidative effects of HZTF may partially account for the underlying mechanism. NO and ROS, which are affected by the activation of the arachidonic acid pathway [ 58 , 59 ], were also significantly inhibited by HZTF as demonstrated in our in vitro experiments.…”
Section: Discussionsupporting
confidence: 70%
“…But experiments have produced contrasting results. Some show that the increase in [Ca 2+ ]i is produced by acidification, in line with expectations given the chemical properties described above [Orchard 1987, Kim 1988, Cairns 1993, Daugirdas 1995, Donoso 1996, Nishiguchi 1997, Nagaoka 1997, González 1998, Balnave 2000, Chen 2001, Thomas 2002, Marin 2010, Krizaj 2011, Paillamanque 2016, Behera 2018, Berra-Romani 2019. Other results, on the contrary, have shown that the increase in [Ca 2+ ]i is produced by alkalinization [Kiang 1991, Guse 1994, Nitschke 1996, Lindeman 1998, Minelli 2000, Alfonso 2000, Li 2012.…”
Section: H + /Ca 2+ Interdependence In the Cellsupporting
confidence: 78%
“…The protons produced by the dissociation of the IP3, following hydrolysis of PIP2, can reduce the affinity of Ca 2+ for binders, such as inorganic anions or proteins, which immobilize it in the cytosol, and can foster the release of Ca 2+ triggering rapid calcium spikes. It has been shown experimentally that the stimulus causes in the cytosol an increased concentration of protons and, in parallel, of Ca 2+ [Kim 1988, Daugirdas 1995, Paillamanque 2016, Behera 2018, Berra-Romani 2019. The cellular control mechanisms and first of all the cytosolic buffering capacity respond equally quickly, ending the spikes and returning the situation to a stationary state.…”
Section: The Dual Molecular Mechanism For Ip3 Triggeringmentioning
confidence: 99%
“…Finally, ex vivo ECFC expansion could be achieved by stimulating an increase in intracellular Ca 2+ concentration ([Ca 2+ ] i ), which has long been known to stimulate ECFC proliferation [ 159 , 160 , 161 , 162 ]. For instance, the liposomal delivery of nicotinic acid adenine dinucleotide phosphate (NAADP), the physiological agonist of endolysosomal two-pore channels (TPCs) [ 163 , 164 , 165 , 166 ], stimulated ECFC proliferation in a Ca 2+ -dependent manner [ 15 ]. Likewise, the lipid messenger arachidonic acid promoted ex vivo ECFC expansion by inducing extracellular Ca 2+ entry through Transient Receptor Potential Vanilloid 4 (TRPV4) channel and then recruiting the endothelial NO synthase (eNOS) [ 167 , 168 ].…”
Section: Manipulation Of Pro-angiogenic Signaling Pathways To Imprmentioning
confidence: 99%